Legal Responsibility of the Regional Supervisory Council of Notaries for Sanctioning a Written Reprimand to a Notary Contrary to the Norms of Article 53 Paragraph (2) of the Law on State Administrative Courts - Eka Aprilia; Rasji (Journal of Law, Politic and Humanities, 2024)
This research aims to determine the legal responsibility of the notary regional supervisory board which has given a written warning sanction to the notary which is contrary to the norms of Article 53 paragraph (2) of the PTUN Law and to find out the legal remedies that the notary can take against the decision of the notary regional supervisory board which has been stated wrong by the PTUN according to Notarial Legal Perception. The research method used is normative juridical legal research. The results of the research show that the legal responsibility of the Notary MPW in giving written warning sanctions to notaries must be carried out carefully and under provisions aimed at maintaining the integrity of the notary profession, protecting the rights of notaries, and ensuring that the supervision process is carried out objectively and transparent. Notaries disadvantaged by MPW decisions declared wrong by the PTUN have several legal routes that can be taken to defend their rights. This step includes filing an appeal, a civil lawsuit, and efforts to rehabilitate the good name. Notaries need to follow proper legal procedures and obtain adequate legal advice to optimize the chances of success in their legal efforts. This legal route reflects justice and protection of notary rights in the notarial legal system in Indonesia